Efeito da ocitocina intranasal sobre sintomas de abstinência em mulheres usuárias de cocaína : ensaio clínico duplo-cego randomizado - Pereira, João Vítor Nóbrega e Mélo (2020)
Introduction: the cocaine use disorder (CUD) is a severe disease, especially among women, who develop more serious consequences of the addiction. Cocaine withdrawal components, such as craving and depressive symptoms, may impact negatively the course of the disease. The neuropeptide Oxytocin (OC) has shown positive effects on cocaine withdrawal symptoms through animal studies, and has been used in humans with safety in the treatment of other medical conditions. Objectives: to evaluate the effect of intranasal OC on cocaine withdrawal symptoms of women with CUD, using a randomized double-blind placebo-controlled trial. Methods: 83 female inpatients with CUD were randomly allocated to 3 experimental conditions: conventional treatment plus intranasal OC administration twice daily (OCT), conventional treatment plus intranasal placebo solution administration twice daily (PBO) and conventional treatment only (CON). The participants underwent a diagnostic interview (SCID 5), evaluation of the severity of the addiction (ASI-6) and intelligence (WASI). The OC or placebo intervention comprised the period between days 8 and 17 from admission. The withdrawal (CSSA) and depressive (QIDS-SR) symptoms were assessed before (T1), during (T2) and after (T3) the intervention. Results: intranasal OC reduced withdrawal symptoms compared to placebo and conventional treatment. This effect was mediated by an improvement on appetite and mood symptoms. Analysis of the instrument specific for depression (QIDS-SR) showed similar results. Both OCT and PBO groups improved depressive symptoms, but women under OCT condition showed greater improvement on the course of detoxification. Conclusion: these results support previous animal studies evidences of positive effects of OC on cocaine withdrawal, adding to the hypothesis that OC exerts its effects on withdrawal symptoms through mood regulation circuits and reward system interactions.